NILAI-NILAI PENDIDIKAN DALAM NOVEL MAMAK KARYA NELSON ALWI - Nindy Elneri; Harris Effendi Thahar; Abdurahman Abdurahman (Universitas Andalas, 2018)
The purpose of this study is to explain the values of religious education in Nelson Alwi's Mamak novel; describing the values of toughness education in Nelson Alwi's Mamak novel; and describing the values of caring education in Nelson Alwi's Mamak novel. This type of research is a qualitative study by using descriptive method of analysis. The data source in this research is Nelson Alwi's novel Mamak. The results of research on the values of education contained in Nelson Alwi's novel Mamak are as follows: (1) the value of religious education, (2) the values of education toughness, and (3) The values of education awareness. The overall data amounted to 46 data. Of these three values, the highest value is the value of awareness education.Keywords: educational value, novel, Nelson Alwi